IDENTITY CHANGE OF CHARACTERS IN GASTON LEROUX’S THE MYSTERY OF THE YELLOW ROOM - Ilham Gusti Permana (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
Abstract This research aims to present a description of the three characters’ identities named Ballmeyer, Joseph Jasphine, and Nona Mathilde Stangerson. It describes the relationship between the identity changes of the three characters depicted in the story. This reseach also describes the factors that cause a person to change his identity. The theory used is meth, namely the theory of direct definition and indirect presentation, using two method approaches, intrinsic and extrinsic approaches. The conclusion of this study shows that the two main male characters experience several changes in their identities while one female character does not experience changes in identity. Keywords: Mystery, Yellow, Room, Identity, Pergantian Identitas, Characters